The Effects of Morinda citrifolia (Noni) Fruit Juice on the Prevention of Stroke by Promoting Production of Nitric Oxide through the Brain of the Spontaneously Hypertensive Stroke Prone (SHRSP) Rats - Kudo, Maya; Yoshitomi, Hisae; Nishigaki, Toshiaki; Gao, Ming (Journal of Nutritional Therapeutics, 2018)
Morinda citrifolia (Noni) is a traditional folk medicinal plant and has a long history of use as a food and medicine. In order to reveal the effects of Noni fruit juice (NFJ) on stroke prevention, we performed experiments using spontaneously hypertensive stroke prone (SHRSP) rats. NFJ did not change rat body weight, food intake, and water intake. However, both systolic blood pressure (SBP) and diastolic blood pressure (DBP) were significantly decreased after NFJ treatment in SHRSP rats. Furthermore, NFJ significantly increased the survival rate, urinary nitric oxide (NO) concentration was significantly higher in the NFJ group, and endothelial NO synthase (eNOS) phosphorylation levels increased in the brain after NFJ treatment. Two pathways regulate eNOS phosphorylation: the insulin-dependent pathway and the insulin-independent pathway. For the insulin-dependent pathway, phosphorylation of insulin receptor substrate 1 (IRS1) and protein kinase B (Akt) did not change in the NFJ group. For the insulin-independent pathway, expression of adenosine monophosphate-activated protein kinase (AMPK) phosphorylation, liver kinase B 1 (LKB1), and silent information regulator 1 (Sirt1) significantly increased in the brain of SHRSP rats after NFJ treatment. These data suggested that NFJ prevented stroke by improved blood circulation, increased NO production, and elevated eNOS phosphorylation by stimulating the insulin-independent pathway (Sirt1-LKB1-AMPK-eNOS).